M-Banking: Perspective in Indian Business - Singh, Naib (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2015)
Mobile banking in India is gaining more and more popularity in the present scenario. India is occupying the position of second largest mobile market in the world after China. The major finding of the study is that the future of mobile banking in India will be bright and certainly be more helpful in the development of banking sector. Our country is having vast access of mobile phone services as compared to developed European countries. In the year 2013 22.51 million people were using these services. The objective of the anytime banking can easily be obtained by mobile banking.